The Character of Students' Love for Their Homeland on Electronic Modules Assisted by Assemblr Edu in Learning - Syahrial; Asrial; Sabil, Husni; Kurniawan, Dwi Agus; Perdana, Rahmat; Rivani, Putri Ayu; Widodo, Rido Ilham (International Journal of Elementary Education, 2023)
The current problem is that the character of loving the homeland still needs to be higher. Lowering the character of love for the motherland impacts student behaviour which is not good. Various types of media are needed to encourage students to learn. The purpose of this study was to analyze the influence of students on the character of loving the motherland by using an electronic module. This study uses a type of quantitative research. The research subjects were taken as many as 19 people from each class. Methods of data collection using observation and questionnaires. The instrument used in this study was a questionnaire sheet. This study uses a simple random technique. The data analysis used was the T-test, regression, and descriptive statistical tests. The study results show an influence between the use of e-modules and the character of loving the motherland in students. It was concluded that using e-modules can improve students' character of loving the motherland. The better and more electronic modules containing nature and the atmosphere in Indonesia, the more the student's sense of love for their homeland will increase.